Evacuation System in a Building Using Cellular Automata for Pedestrian Dynamics - ., Muarifin; Harsono, Tri; Barakbah, Aliridho (Politeknik Elektronika Negeri Surabaya (PENS), 2015)
The sense of safety in public facilities for pedestrians can be shown by the availability of good infrastructure, particularly the building. One of the aspects that can make pedestrians feel comfortable and safe is the availability of evacuation facilities in emergency situation. When a disaster strikes, people would start to panic and this will cause problems, especially during an evacuation.During panic in an evacuation process, pedestrians tend to act blindly and walk randomly and mindlessly. They might follow one another when they get panic. This is called as herding behavior. Regarding the evacuation systems, cellular automata is the basic method used to represent human motion. The movement of pedestrian is an important aspect during an evacuation process and this can be analyzed and implemented by using Cellular Automata. It is a simple method yet it can solve complex problems.Total evacuation time becomes the indicators in measuring the efficiency of this system. The result of comparison method shows that the proposed method could work better in certain conditions. In addition, the results of the experiments during panic and normal situation show similar characteristics especially regarding density aspect, yet evacuation time during panic situation takes longer time. The experimentâs results by using the actual data also has similar tendency with the evacuation time.Keywords: evacuation time, cellular automata, panic behavior,Â pedestrian